2018
DOI: 10.1186/s12263-018-0609-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cellular network of metabolic flexibility in the adipose tissue

Abstract: BackgroundMetabolic flexibility is the ability of cells to change substrates for energy production based on the nutrient availability and energy requirement. It has been shown that metabolic flexibility is impaired in obesity and chronic diseases such as type 2 diabetes mellitus, cardiovascular diseases, and metabolic syndrome, although, whether it is a cause or an effect of these conditions remains to be elucidated.Main bodyIn this paper, we have reviewed the literature on metabolic flexibility and curated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Metabolic flexibility gene list. In a previous study 20 , we explored the cellular processes involved in cellular metabolic flexibility and presented them as a combined network of rate limiting steps involved in these processes. In the current study, we utilised the network and processes from this review to curate a list of genes/proteins involved in the regulation of cellular metabolic flexibility.…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic flexibility gene list. In a previous study 20 , we explored the cellular processes involved in cellular metabolic flexibility and presented them as a combined network of rate limiting steps involved in these processes. In the current study, we utilised the network and processes from this review to curate a list of genes/proteins involved in the regulation of cellular metabolic flexibility.…”
Section: Proteomicsmentioning
confidence: 99%
“…The purpose of this exercise is to identify and analyse expression profiles of individuals clustered by cellular metabolism centring on metabolic flexibility. In our previous studies 9,20,21 , we have shown how the cellular regulation of the tricarboxylic acid cycle, as well as the switching of substrates between glucose and fatty acids have a central role to play in obesity and chronic ailments such as type 2 diabetes mellitus and metabolic syndrome. Capitalising on this work, we curated a list of 291 genes involved in, or associated with the regulation of, cellular metabolism and substrate switching.…”
mentioning
confidence: 99%
“…Investigations by many laboratories over the past several decades emphasized the integral role of the mitochondrial pyruvate dehydrogenase complex (PDC) in regulating fuel metabolism and organismal homeostasis in health and during both physiologic and pathologic stress . Under aerobic conditions, PDC catalyzes the rate‐determining step in aerobic glucose oxidation by irreversibly decarboxylating glycolytically derived pyruvate to acetyl coenzyme A (acetyl‐CoA), which condenses with oxaloacetate to form citrate in the tricarboxylic acid (TCA) cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review [5], we explored the various cellular processes involved in maintaining cellular metabolic flexibility in the adipose tissue. The two major energy production mechanisms, glycolysis and fatty acid oxidation, are tied to the TCA cycle – glycolysis through the production of pyruvate and its conversion to acetyl coenzyme A (acetyl-CoA), and fatty acids through their breakdown to acyl coenzyme A and transportation into the mitochondria through the carnitine transport mechanism for eventual conversion to acetyl-CoA.…”
Section: Introductionmentioning
confidence: 99%